2020
DOI: 10.7759/cureus.10572
|View full text |Cite
|
Sign up to set email alerts
|

Sort, Assess, Life-Saving Intervention, Triage With Drone Assistance in Mass Casualty Simulation: Analysis of Educational Efficacy

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In this, a fast reaction, sufficient coordination, and the accessibility of innovative biodosimetry is required. Clinical triage following an atomic explosion ought to be a stepwise cycle, where the principal point is abbreviated as “SALT”- Sort, Assess, Lifesaving Interventions, Treatment/Transport [ 29 ]. In the military, operational organizers use ‘parts’ to characterize the four levels where military clinical help is coordinated on a reformist premise to lead triage evaluation, quick treatment, evacuation, resupply, and capacities basic to the upkeep of health [ 30 ].…”
Section: Triage and Categorizationmentioning
confidence: 99%
“…In this, a fast reaction, sufficient coordination, and the accessibility of innovative biodosimetry is required. Clinical triage following an atomic explosion ought to be a stepwise cycle, where the principal point is abbreviated as “SALT”- Sort, Assess, Lifesaving Interventions, Treatment/Transport [ 29 ]. In the military, operational organizers use ‘parts’ to characterize the four levels where military clinical help is coordinated on a reformist premise to lead triage evaluation, quick treatment, evacuation, resupply, and capacities basic to the upkeep of health [ 30 ].…”
Section: Triage and Categorizationmentioning
confidence: 99%
“…Researchers (2020), in a systematic review of 22 articles published from 2015 to 2019 about the use of simulators in the diagnosis of diseases, showed that artificial intelligence techniques were an excellent method in diagnosing chronic diseases that could affect the quality of patient care and reduce medical costs. [ 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…Artificial intelligence algorithms are currently being used to enable faster prediction and diagnosis of diseases and improve patients' outcomes. [ 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 97 included articles, 13110 47 discussed competencies, 1619,24,2939,4144,4655,71,84,90,91,95,96,99,100,103110 and were split between 2 authors to extract data into an Excel database (Microsoft Corp., Redmond, Washington, USA) that was developed using themes and subthemes from MCI exercise publications to derive statements for the mD. 111–115 (Supplemental Digital Content link to Excel database)…”
Section: Methodsmentioning
confidence: 99%
“…13110 Specifically discussing competencies. 1619,24,2939,4144,4655,71,84,90,91,95,96,99,100,103110 …”
Section: Introductionmentioning
confidence: 99%